2017
DOI: 10.1139/cjfr-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Species comparison of the physical properties of loblolly and slash pine wood and bark

Abstract: Composition of the southern pine forest is now predominated by two species, loblolly pine (Pinus taeda L.) and slash pine (Pinus elliottii Engelm.), owing to fire suppression activities, natural regeneration on abandoned agricultural lands, and extensive planting. Comparison of the wood and bark physical properties of these pines is of interest in terms of the yields of usable biomass and, for the bark, its ecological functionality on a living tree. Trees from a species comparison study were used to generate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 32 publications
5
13
6
Order By: Relevance
“…The average bark mass reported in this study (19%) was larger than that reported by Eberhardt et al (2017) for Pinus taeda (12.5%) and Pinus elliottii (17%). The pattern of variation of bark mass and bark thickness were in agreement with that reported by Quilhó and Pereira (2001) and Cellini et al (2012): bark mass was site independent and increased with relative height up the stem.…”
Section: Discussioncontrasting
confidence: 80%
“…The average bark mass reported in this study (19%) was larger than that reported by Eberhardt et al (2017) for Pinus taeda (12.5%) and Pinus elliottii (17%). The pattern of variation of bark mass and bark thickness were in agreement with that reported by Quilhó and Pereira (2001) and Cellini et al (2012): bark mass was site independent and increased with relative height up the stem.…”
Section: Discussioncontrasting
confidence: 80%
“…Given the rapid growth rate and high defect rate, there are questions about the quality of planted longleaf pine and how it relates to current perceptions of longleaf pine, which are based on slow growing and naturally regenerated longleaf pine. A significant amount of information is available on the wood and fiber quality of planted loblolly pine (Mora et al 2007;Jordan et al 2008;Antony et al 2015;Dahlen et al 2018;Schimleck et al 2018), and to a lesser extent slash pine (Eberhardt et al 2017), however, there is little information available on the wood quality of planted longleaf pine. The wood quality information on planted longleaf pine that does exist (Baldwin and Saucier 1983;Gibson et al 1986;Clark and Schmidtling 1989) was measured prior to the recent restoration efforts and had much higher planting densities (2470 trees ha -1 to 3700 trees ha -1 ) (Baldwin and Saucier 1983;Gibson et al 1986) compared to current practices for establishing planted longleaf pine (1235 trees ha -1 ) (South 2006).…”
Section: R a F Tmentioning
confidence: 99%
“…(MC) of the wood and bark is important (Eberhardt et al 2017). Bark is typically burned for energy, however bark properties are also of interest with regards to other bioenergy applications and for bioproducts (Baker et al 2012).…”
Section: R a F Tmentioning
confidence: 99%
See 2 more Smart Citations